2019
DOI: 10.18332/tid/104753
|View full text |Cite
|
Sign up to set email alerts
|

Smoker perceptions of health warnings on cigarette packaging and cigarette sticks: A four-country study

Abstract: INTRODUCTIONInnovations in tobacco control interventions are required to ensure continued reductions in global tobacco use, and to minimise attributable morbidity and mortality. We therefore aimed to investigate the perceived effectiveness of current cigarette packaging warnings and the potential effectiveness of cigarette-stick warnings across four countries.METHODSAn online survey was distributed to adult smokers in Australia, Canada, the United Kingdom, and the United States. Participants rated (using a 5-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 41 publications
2
22
0
Order By: Relevance
“…Five of the studies raised minor methodological concerns 22 , 24–26 , 29 and two major methodological concerns. 27 , 28 Table 2 summarizes the direction of effect and/or key findings for the results of the studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five of the studies raised minor methodological concerns 22 , 24–26 , 29 and two major methodological concerns. 27 , 28 Table 2 summarizes the direction of effect and/or key findings for the results of the studies.…”
Section: Resultsmentioning
confidence: 99%
“…Increase in warning salience at Wave 2 was greater in England than in other six countries. Drovandi et al 27 Cross-sectional online survey Jun 2018 (approx. one year after end of transition period) Smokers 19–74 years UK, Australia, Canada, USA n=155 UK n=532 other countries Smokers in UK (UK standardized packs) vs smokers in Australia, Canada, USA (each countries’ own packs) Favors UK standardized packs (perceived effectiveness of warnings in prompting smokers to quit).…”
Section: Resultsmentioning
confidence: 99%
“… 2018 ; Drovandi et al. 2019a , 2019b , 2019c ). Given that some participants suggested that they would switch to rolling tobacco or use rolling tobacco papers to cover warnings on cigarettes, research with smokers of rolling tobacco would be fruitful, particularly in markets where this product has a significant share of the tobacco market.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that the findings were influenced by socially desirable responding. As wear-out is an issue with all warnings (Fischer et al 1993), with habituation raised within the groups, future research should consider additional, appropriate warning messages (Drovandi et al 2018;Drovandi et al 2019aDrovandi et al , 2019bDrovandi et al , 2019c. Given that some participants suggested that they would switch to rolling tobacco or use rolling tobacco papers to cover warnings on cigarettes, research with smokers of rolling tobacco would be fruitful, particularly in markets where this product has a significant share of the tobacco market.…”
Section: Discussionmentioning
confidence: 99%
“…18 According to a study by Drovandi et al, done in Australia, Canada, UK and US smokers found cigarette packet warning minimally effective in prompting smokers to quit. 19 In a systemic review done by Noar et al, it was found that with strengthening the cigarette pack warnings cigarette consumption decreased in three of the eight studies, quit attempt increased in four of the seven studies and smoking prevalence decreased in six of the nine studies. 20 In the present study also it was found that 84.8% of the subject had no effect of HW on their smoking habit.…”
Section: Discussionmentioning
confidence: 98%